17α-ethynilestradiol and tributyltin mixtures modulates the expression of NER and p53 DNA repair pathways in male zebrafish gonads and disrupt offspring embryonic development. (December 2018) - Soares, Joana; Neuparth, Teresa; Lyssimachou, Angeliki; Lima, Daniela; André, Ana; Reis-Henriques, Maria A.; Castro, Luís Filipe C.; Carvalho, António Paulo; Monteiro, Nuno M.; Santos, Miguel M.
Highlights: Parental exposure to EE2 and EE2 plus TBT impairs zebrafish embryonic development. EE2 and TBT, single and combined, modulate key DNA repair genes. p53 gene expression in male gonads reflects embryonic development disruption data. Mixtures of the selected compounds produce chiefly unpredictable effects. Abstract: Although chemicals are usually present in the environment in complex mixtures, ecotoxicological risk assessments often rely on data from single exposures to contaminants. The present study aimed at examining the effects of two ubiquitous endocrine disrupting chemicals (EDCs), 17α-ethynilestradiol (EE2 ) and tributyltin (TBT), single and combined, in zebrafish ( Danio rerio ) reproduction and embryonic development, and to investigate the impact on DNA repair molecular pathways. Chronic life-cycle exposure to environmental relevant concentrations of both EDCs led to significant effects on reproduction and embryonic development. TBT exposure at 50 ng/L impacted the percentage of fertilized eggs. EE2 exposure at 0.75 and 1.75 ng/L and the mixture treatments (0.75 and 1.75 ng/L EE2 plus 50 ng/L TBT) led to a sex bias towards females. Furthermore, EE2 exposure at 1.75 ng/L and the mixture of EE2 (1.75 ng/L) and TBT (50 ng/L) impaired embryonic development. The study of DNA repair pathways indicated that EE2 and TBT, single and combined, significantly modulated the expression levels of key DNA repair genes in male gonads, such as xpc nucleotide excision repair (NER) pathway gene as well as the tumor suppressor p53, its target effectors, i.e. p21, gadd45α and bax, and p53 key regulator ( mdm2 ). The observed impact in the transcription of these genes supports the hypothesis of an effect of EE2, TBT, and their combined mixtures, on DNA repair pathways, thus suggesting that impairment of embryonic development of F2 generation could be linked to the disruption of DNA repair processes in the gonads of individuals from the parental generation. Taken together, these findings contribute to a better understanding of the impact of mixtures of the ubiquitous contaminants EE2 and TBT, strongly supporting the inclusion of embryonic development and gene expression studies in the screening of endocrine disruption in wildlife.